2021
DOI: 10.4103/jpbs.jpbs_337_19
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ultra Performance Liquid Chromatography-PDA Method Development and Validation for Darunavir in Bulk and Its Application to Marketed Dosage Form

Abstract: A BSTRACT Aims and Objective: The aim of this study was to develop and validate a novel ultra-performance liquid chromatographic method for estimation of darunavir in a bulk and tablet dosage form. Materials and Methods: The chromatographic separation was achieved using DIKMA Endoversil (2.1mm x 50mm, 1.7 µm) column. A mixture of 40% buffer (0.1% octa sulfonic acid) and 60% acetonitrile was used as a mobile phase with the isocratic elution mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…So far, only a few analytical techniques have been published for the chromatographic analysis of combination formulation, either separately or together. According to the literature review (Abduljalil & Badhan, 2016;Chiranjeevi & Channabasavaraj, 2011;Ettaboina et al, 2022;Grace & Parthiban, 2022;Jagadeeswaran et al, 2012;Kashish et al, 2020;Kavitha, 2020;Kumar et al, 2016;Lathouwers et al, 2011;Masaaki et al, 2021;Mishra & Shrivastav, 2014;Muchakayala et al, 2022;Pappula & Naresh, 2022;Patel et al, 2013;Paul et al, 2021;Raju et al, 2021;Rezk et al, 2009;Sabyasachi et al, 2021) none of these methods was found suitable for a stability-indicating analysis for quality control use.Thelonger run time used for quantification makes methods time consuming and cost-effective. In general, the technique should be enhanced or its robustness should be proven using the quality by design (QbD) approach, according to the present regulatory criteria, which are unambiguous.…”
mentioning
confidence: 99%
“…So far, only a few analytical techniques have been published for the chromatographic analysis of combination formulation, either separately or together. According to the literature review (Abduljalil & Badhan, 2016;Chiranjeevi & Channabasavaraj, 2011;Ettaboina et al, 2022;Grace & Parthiban, 2022;Jagadeeswaran et al, 2012;Kashish et al, 2020;Kavitha, 2020;Kumar et al, 2016;Lathouwers et al, 2011;Masaaki et al, 2021;Mishra & Shrivastav, 2014;Muchakayala et al, 2022;Pappula & Naresh, 2022;Patel et al, 2013;Paul et al, 2021;Raju et al, 2021;Rezk et al, 2009;Sabyasachi et al, 2021) none of these methods was found suitable for a stability-indicating analysis for quality control use.Thelonger run time used for quantification makes methods time consuming and cost-effective. In general, the technique should be enhanced or its robustness should be proven using the quality by design (QbD) approach, according to the present regulatory criteria, which are unambiguous.…”
mentioning
confidence: 99%